2006
DOI: 10.1016/j.ydbio.2006.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Components of both major axial patterning systems of the Bilateria are differentially expressed along the primary axis of a ‘radiate’ animal, the anthozoan cnidarian Acropora millepora

Abstract: Cnidarians are animals with a single (oral/aboral) overt body axis and with origins that nominally predate bilaterality. To better understand the evolution of axial patterning mechanisms, we characterized genes from the coral, Acropora millepora (Class Anthozoa) that are considered to be unambiguous markers of the bilaterian anterior/posterior and dorsal/ventral axes. Homologs of Otx/otd and Emx/ems, definitive anterior markers across the Bilateria, are expressed at opposite ends of the Acropora larva; otxA-Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 46 publications
0
53
0
Order By: Relevance
“…For example, strictly aboral orientation of early ectodermal neurites in the hydrozoan Podocoryne is restricted to neurons in the oral region (Groger and Schmid, 2001;Momose and Schmid, 2006), whereas RFamide-positive ectodermal neurites in the scyphozoan Aurelia (Nakanishi et al, 2008) and the anthozoan Acropora millepora (Hayward et al, 2001) develop oral and aboral projections. Similarly, the extensive endodermal nervous system development in planulae observed in N. vectensis has not been described in other cnidarians (de Jong et al, 2006;Groger and Schmid, 2001;Martin, 2000;Nakanishi et al, 2008;Piraino et al, 2011). Additional studies of nervous system formation at high temporal and spatial resolution in these and other cnidarians are needed for a detailed reconstruction of the evolutionary histories of cnidarian neural development.…”
Section: Evolution Of Cnidarian Nervous System Developmentmentioning
confidence: 96%
“…For example, strictly aboral orientation of early ectodermal neurites in the hydrozoan Podocoryne is restricted to neurons in the oral region (Groger and Schmid, 2001;Momose and Schmid, 2006), whereas RFamide-positive ectodermal neurites in the scyphozoan Aurelia (Nakanishi et al, 2008) and the anthozoan Acropora millepora (Hayward et al, 2001) develop oral and aboral projections. Similarly, the extensive endodermal nervous system development in planulae observed in N. vectensis has not been described in other cnidarians (de Jong et al, 2006;Groger and Schmid, 2001;Martin, 2000;Nakanishi et al, 2008;Piraino et al, 2011). Additional studies of nervous system formation at high temporal and spatial resolution in these and other cnidarians are needed for a detailed reconstruction of the evolutionary histories of cnidarian neural development.…”
Section: Evolution Of Cnidarian Nervous System Developmentmentioning
confidence: 96%
“…In metamorphosing planulae of the anthozoan A. millepora, the decrease in the number of ectodermal cells expressing emx-Am and RFamide has been reported (de Jong et al 2006), suggesting the degeneration of the planula nervous system. de Jong et al also reported a drastic reversal of Pax3/7-like Pax-Dam expression from the anterior/aboral to posterior/oral end associated with the metamorphosis.…”
Section: Metamorphosismentioning
confidence: 99%
“…Accordingly, several of the Otx downstream targets are extracellular cell-adhesion molecules and actin/myosin-binding proteins (Bellipanni et al 2000;Boncinelli and Morgan 2001;Yuh et al 2001), and some of these Otx targets apparently mediate convergentextension movements during gastrulation in vertebrate embryos (Boncinelli and Morgan 2001). The expression of Otx in Hydra is also associated with morphogenetic events (Smith et al 1999), and Otx expression in the anthozoan A. millepora relates to the blastopore, while it is not expressed in the endoderm (de Jong et al 2006); the combination of both cnidarian reports suggests that Otx gastrulation functions were already present in the last common ancestor of bilaterians and cnidarians. The Otx expression in a leech Helobdella triserialis (Bruce and Shankland 1998), a polychaete (Arendt et al 2001), and an indirectly developing gastropod (Nederbragt et al 2002) also correlates with the foregut, although no midgut expression was described in any of these embryos.…”
Section: Heotx Expression Correlates With Gastrulation Midgut and Fomentioning
confidence: 99%
“…To our knowledge, no endomesoderm role has been reported for Otx orthologs among ecdysozoans. In the anthozoan Acropora millepora, the Otx ectoderm expression and its association with the blastopore (de Jong et al 2006) would suggest that the ancestral role in the last common ancestor of bilaterians and cnidarians relates more to gastrulation than to endoderm cell-type specification; however, the expression in the striated muscle of the medusa stage in another cnidarian (Muller et al 1999) raises uncertainties about the ancestral cnidarian germ layer association.…”
Section: Introductionmentioning
confidence: 99%